2016
DOI: 10.1002/pmic.201500321
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel serum peptides biomarkers for female breast cancer patients in Western China

Abstract: This study aimed to identify novel serum peptides biomarkers for female breast cancer (BC) patients. We analyzed the serum proteomic profiling of 247 serum samples from 96 BC patients, 48 additional paired pre- and postoperative BC patients, 39 fibroadenoma patients as benign disease controls, and 64 healthy controls, using magnetic-bead-based separation followed by MALDI-TOF MS. ClinProTools software identified 78 m/z peaks that differed among all analyzed groups, ten peaks were significantly different (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Mass spectrometry (MS) combined with software-generated models can be used to compare the proteomic profiles of cancer patients and healthy individuals quickly and accurately [ [4] , [5] , [6] ]. In the past few years, there have been many reports of the development of diagnosis or prognosis models and screening of new peptide biomarkers of CRC, however, these models and biomarkers have not been applied to clinical practice due to variation in sensitivity and specificity [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry (MS) combined with software-generated models can be used to compare the proteomic profiles of cancer patients and healthy individuals quickly and accurately [ [4] , [5] , [6] ]. In the past few years, there have been many reports of the development of diagnosis or prognosis models and screening of new peptide biomarkers of CRC, however, these models and biomarkers have not been applied to clinical practice due to variation in sensitivity and specificity [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Such, the BC patients and healthy controls were compared for differences in serum proteome via SELDI-TOF-MS, and identified that apolipoprotein CI and complement C3a desArg were up-regulated in sera of patient set ( Chung et al, 2014 , Opstal-van Winden et al, 2011 ). In order to estimate the discriminatory power of putative markers sufficiently, the investigators added benign disease controls comprising of breast fibroadenoma patients to study sets ( Meng et al, 2011 , Yang et al, 2015 ). Furthermore, the diagnostic accuracy of potential serum biomarkers were also evaluated with the multivariate logistic regression analysis ( Lumachi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of reasons for fibrinogen upregulation, of which malignant tumor accounts for 20% based on a Chinese article. Previous studies indicate that the serum level of FGA is upregulated in many tumors, such as gastric cancer, breast cancer, nasopharyngeal carcinoma, acute lymphocytic leukemia, esophageal squamous cell carcinoma, and renal cell cancer (31)(32)(33)(34)(35). The abnormal expression of FGG was also reported in hepatocellular carcinoma and ovarian cancer (36).…”
Section: Discussionmentioning
confidence: 91%